Resilience, Psychological Distress, and Self-Esteem among Undergraduate Students in Kollam District, Kerala - Harikrishnan U.; Arif Ali (Journal of Social Work Education and Practice, 2023)
Resilience decrease the risk of psychological distress enhances self-esteem, it also helps in developing effective coping mechanisms when faced with stress and trauma. The study aimed to assess resilience, psychological distress, and self-esteem among the undergraduate students in Kollam district, Kerala. A cross-sectional study among undergraduate students from arts and commerce background was selected through a purposive sampling method. Total enumeration method was used for the selection of college students. A total of 411 students participated in the study, only 294 students were included in the analysis due in-complete perform. Regression model, self-esteem variables contributed significantly to the prediction of overall resilience of undergraduate students (F (4,289) = 6.942, pp<.05 accounting for 8.8 percent variance. Self-esteem strongly contributed to the difference in the overall resilience score (Beta=-.269, t=4.629 p=.000). Psychological distress and self-esteem among university students is associated with resilience; it is essential to promote resilience among university students. The ability of the students to adapt skillfully and cope with stressors in college and university depends upon the level of resilience. Findings of the study show that there is a need to develop resilience-based interventions among university students to prevent psychological distress.